Hemorheologic profile in patients with angina pectoris - Botas, L. (2015)
Thirteen patients (9 men and 4 women) with stable angina, whose ages ranged from 48 to 62 years (mean 57 years), were studied in order to establish the hemorheologic profile consequent to effort as well as some parameters of the oxygen transport system. The results were compared with those obtained from a control group of 8 healthy individuals, 4 men and 4 women, whose ages ranged from 40 to 57 years (mean 48 years). The patients presented values of P50 in vivo during rest (R) higher than the control group (p < 0.05); the filtration time of blood (FT) and the flow rate of erythrocyte filtration (FR) rose significantly from the R to the precocious recovery (Rec) phase, both in the control group (p < 0.01) and in the patients (p < 0.001). There was, therefore, no remarkable difference in these parameters as well as in arterial pH, Hb and Ht at rest and after maximum effort, between the patients and the control group. The lactate presented higher values (p < 0.05) in the control group when only early phase of Rec was taken into account. In the patients there was a significant positive correlation during rest between 2,3-DPG and FT (p < 0.05) and between PSOiv and FT (p < 0.02). This correlation was not found in the control group. It was also found a significant rise of Hi in the early phase of Rec among the patients as opposed to the control group. The results suggest: (a) adaptation of the oxygen transport system in the patients with angina through a rise of oxyhemoglobin dissociation capacity; (b) aggravation of hemorheologic profile after effort, more conspicuous in the patients than in the control group; (c) the system of oxygen transport in the patients seems to be influenced by alterations of hernoiheologic parameters.